The fall of the Roman Republic - Shotter, D. C. A. (David Colin Arthur) (Lancaster pamphlets in ancient history., 2005)
Revised and updated to include the latest research in the field, this second edition of a popular history text examines how the Roman republic was destabilized by the unplanned growth of the Roman Empire. Central discussion points include:the government of the republichow certain individuals took advantage of the expansion of the empireJulius Caesar's accession to powerthe rise of the Augustan principate following Julius Caesar's murder. Drawing on a wealth of recent scholarship and including an expanded and updated guide to further.